Model Integratif Antara Emotional Intelligence, Psychological Capital Dimediasi Job Crafting Dalam Meningkatkan Performance Kerja Hybird Di RSUD Kabupaten Sorong - Yunita Abidin Nanulaitta; Salim Basalamah; Etik Prihatin (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
This study aims to analyze the integrative model between emotional intelligence and psychological capital, mediated by job crafting, in improving hybrid work performance of employees at Sorong Regency General Hospital. The study sample consisted of 57 employees selected as respondents. This study used a quantitative approach with a survey method, and data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM) techniques through the SmartPLS application. The results of the study indicate that emotional intelligence has a positive and significant effect on job crafting. Psychological capital has a positive and significant effect on job crafting. Emotional intelligence has a positive and significant effect on performance. Psychological capital has a positive and significant effect on performance. Job crafting has no significant effect on performance. Job crafting is unable to mediate the influence of emotional intelligence and psychological capital on performance.. Keywords: Emotional Intelligence, Psychological Capital, Job Crafting Performance.